2006
DOI: 10.1016/j.crci.2006.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of reactive systems in twin-screw extrusion: challenges and applications

Abstract: Reactive extrusion processes involve the difficulties of mastering classical polymer processes, such as twin-screw extrusion for example, and the problems of controlling a chemical reaction in very specific conditions (high-viscosity medium, high temperatures, short residence times). Therefore, it is often very difficult to intuitively understand all the aspects of the process and to clarify the complex interactions between the numerous variables, and then to properly design and optimize the industrial process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 40 publications
0
50
0
Order By: Relevance
“…The horizontal lines correspond to the values expected for each polymer after complete melting, taking into account their relative density and relative percentage. In the feeding zone (screw turns 1-10), the melting rate of the blends is essentially determined by the PP melting rate, whereas in the compression zone (screw turns [11][12][13][14][15][16][17][18][19][20] the role of PA6 seems predominant. Moreover, in the feed zone (screw turns 1-10), the higher the PP content in the blend, the higher the melting rate of this polymer.…”
Section: Example Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The horizontal lines correspond to the values expected for each polymer after complete melting, taking into account their relative density and relative percentage. In the feeding zone (screw turns 1-10), the melting rate of the blends is essentially determined by the PP melting rate, whereas in the compression zone (screw turns [11][12][13][14][15][16][17][18][19][20] the role of PA6 seems predominant. Moreover, in the feed zone (screw turns 1-10), the higher the PP content in the blend, the higher the melting rate of this polymer.…”
Section: Example Of Resultsmentioning
confidence: 99%
“…The above experimental observations and models typically consider processing of homopolymers, or of very simple polymer systems. The study of melting of (immiscible or reactive) polymer blends is much less common and seems to be limited to twin screw extrusion [16][17][18]. It is well known that the morphologies formed upon melting will influence the final morphologies obtained which, in turn, will determine the mechanical properties [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its comparably low computational expense, it is still the only way to develop a simulation of the entire extrusion process. For more detailed information about 1D modeling, please refer to the literature, e.g., (White and Chen, 1994;Potente and Hanhart, 1994;Vergnes et al, 1998;Potente et al, 1999;White et al, 2001;Potente and Kretschmer, 2002;Prat et al, 2002;Choulak et al, 2004;Vergnes and Berzin, 2006;Bahloul et al, 2011;Teixeira et al, 2012;Eitzlmayr et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important reasons for modeling the reactive extrusion systems is to gain an understanding of the kinetics of reactions taking place under the reactive blending process. [4] Melt processing of PET with PEN results in intermolecular exchange reactions (see Scheme 1). Early works revealed that immiscibility of these polymers could be overcome only when the intermolecular exchange reactions leading to the formation of mixed terephthalate-ethylene glycol-naphthalate (TEN) sequences reaches a certain conversion.…”
Section: Introductionmentioning
confidence: 99%